Microwave-assisted extraction of Phenolic Compounds from Pineapple Peel against Staphylococcus aureus and Escherichia coli - Mashuni Mashuni; Fitri Handayani Hamid; M Jahiding; Nur Cahya Islamiati MR; Sitti Hadijah Sabarwati; Andi Muhammad Naufal Khaeri (LPPM ISTEK 'Aisyiyah Kendari, 2024)
Pineapple production is mostly marketed as a processed product, resulting in large amounts of industrial waste consisting of pineapple peel, core and crown. This study evaluated organic solvents for microwave-assisted extraction (MAE) of phenolic compounds from pineapple peel and their total phenolic content and antibacterial activities. The application of microwave technology in phenolic extraction provides a fast extraction process and produces higher yields. In addition, organic solvent ethanol is considered an environmentally friendly solvent characterized by low toxicity and increased capacity to extract bioactive compounds. The solvent compositions are ethanol (80%), ethanol-HCl (80%-5%), and ethanol-NaOH (80%-5%). A higher phenolic compound was obtained using ethanol-HCl (80%-5%) of 2.68 mg eq GA/g DW. The results of the antibacterial activity test against Staphylococcus aureus was 19.00 mm and Escherichia coli was 19.31 mm. These results indicate that pineapple peel extract from ethanol-HCl solvent can be an effective antibacterial agent.